2010
DOI: 10.1080/10874208.2010.523331
|View full text |Cite
|
Sign up to set email alerts
|

Does Neurofeedback Help Reduce Attention-Deficit Hyperactivity Disorder?

Abstract: Introduction: Neurofeedback is an alternative treatment for Attention Deficit Hyperactivity Disorder (ADHD), but its efficacy is unknown. This narrative review examines rigorous studies conducted utilizing neurofeedback as a treatment for ADHD.Methods: Studies were located by searching the Web of Science and PsycINFO databases with the keywords ADHD or attention deficit hyperactivity disorder AND neurofeedback or EEG biofeedback or electroencephalogram biofeedback. Located studies were chosen for initial revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…10 Neurofeedback therefore trains users to monitor and change their brainwave patterns, leading to behavioral changes. 11 Some studies have found that neurofeedback can decrease symptoms of ADHD, [12][13][14][15][16][17] including improved attention, 18 behavior, 19 and cognitive improvements 20 up to 6 months postintervention as well as at 2 years postintervention. 21 However, the evidence for its sustainability remains unclear, because there are limited studies examining follow-up data, and those that do have small sample sizes or no control condition.…”
mentioning
confidence: 99%
“…10 Neurofeedback therefore trains users to monitor and change their brainwave patterns, leading to behavioral changes. 11 Some studies have found that neurofeedback can decrease symptoms of ADHD, [12][13][14][15][16][17] including improved attention, 18 behavior, 19 and cognitive improvements 20 up to 6 months postintervention as well as at 2 years postintervention. 21 However, the evidence for its sustainability remains unclear, because there are limited studies examining follow-up data, and those that do have small sample sizes or no control condition.…”
mentioning
confidence: 99%
“…More specifically, participant children 7 to 12 years of age, who were diagnosed with ADHD, either IA or C subtypes, and who underwent neurofeedback training, showed improved performance on all IVA sub-scales, with exception of the readiness subscale (Table 1 and Table 3). An extensive number of research studies (Arns et al, 2009;Fox et al, 2005;Gani et al, 2009;Gevensebelen et al, 2009;Lofthouse et al, 2010;Monstra et al, 2005;Sherlin et al, 2010;Williams, 2010) support the effectiveness of neurofeedback training on decreasing the clinical symptoms associated with ADHD. In particular, the literature review performed by Sherlin and colleagues (2010) provide evidence of empirical findings supporting the effects of neurofeedback interventions in decreasing ADHD symptoms in all subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature also indicates that most researches (e.g., Arns et al, 2009;Fox et al, 2005;Gani et al, 2009;Gevensebelen et al, 2009;Lofthouse et al, 2010;Monstra et al, 2005;Sherlin et al, 2010;Williams, 2010) have focused on the combined subtype of ADHD, and in follow-up assessments regarding the effectiveness of neurofeedback, on the decline of clinical symptoms; however, these studies have not evaluated the role of neurofeedback in the improvement of cognitive deficits taking into account different subtypes. Hence, given the extreme importance of cognitive deficits in the perseveration and severity of ADHD symptoms (e.g., Butcher et al, 2000;Fischer, Barkley, Smallish, & Fletcher,2005), and given the effectiveness of neurofeedback training in ADHD patients' neuropsychological rehabilitation (e.g., Arns et al, 2009;Fox et al, 2005;Gani et al, 2009;Gevensebelen et al, 2009;Lofthouse et al, 2010;Monastra et al, 2005;Sherlin et al, 2010;Williams, 2010), the aim of the present research was to determine the effectiveness of neurofeedback training in decreasing cognitive deficits considering C and IA subtypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofeedback of ADHD in children and adolescents has recently been reviewed extensively (Arns et al, 2009;Lubar, 2003;Monastra, 2003;Sherlin, Arns, Lubar, & Sokhadze, 2010;J. M. Williams, 2010).…”
Section: Approach To Treatment Of Substance Abusing Adolescents With mentioning
confidence: 99%